2016
DOI: 10.1007/s00381-016-3042-1
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular-subcutaneous shunt for the treatment of experimental hydrocephalus in young rats: technical note

Abstract: An experimental CSF shunt technique was devised. Excessive CSF of hydrocephalic rats is diverted into the subcutaneous space where it can be resorbed. This technique has a low complication rate and is effective. It might be applied to various types of experimental studies involving induction and treatment of hydrocephalus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
0
2
0
10
Order By: Relevance
“…We found that Ccdc39 prh/prh rats developed dome-shaped heads, which indicates that the unfused skull suture might alleviate the elevation in intracranial pressure (ICP) at this neonatal stage (Jones et al, 2000), although ICP is expected to increase once the skull sutures fuse between P12 and P20 (Grova et al, 2012; Roth et al, 1997) and the ventriculomegaly reaches moderate proportions (Jones et al, 2000). Although the prh mutant mouse was useful for identifying the direct defects of motile cilia (Abdelhamed et al, 2018), the small anatomical size of the murine model constrains its use for surgical procedures such as ICP recording (Hiploylee and Colbourne, 2014) and ventricular–subcutaneous shunting (Santos et al, 2016) that can more easily and accurately be performed in rats. Ultimately, the use of these advanced surgical procedures in our larger rodent model of neonatal hydrocephalus can provide new insights into the role of intracranial pressure change in neonatal hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…We found that Ccdc39 prh/prh rats developed dome-shaped heads, which indicates that the unfused skull suture might alleviate the elevation in intracranial pressure (ICP) at this neonatal stage (Jones et al, 2000), although ICP is expected to increase once the skull sutures fuse between P12 and P20 (Grova et al, 2012; Roth et al, 1997) and the ventriculomegaly reaches moderate proportions (Jones et al, 2000). Although the prh mutant mouse was useful for identifying the direct defects of motile cilia (Abdelhamed et al, 2018), the small anatomical size of the murine model constrains its use for surgical procedures such as ICP recording (Hiploylee and Colbourne, 2014) and ventricular–subcutaneous shunting (Santos et al, 2016) that can more easily and accurately be performed in rats. Ultimately, the use of these advanced surgical procedures in our larger rodent model of neonatal hydrocephalus can provide new insights into the role of intracranial pressure change in neonatal hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…3.5 Implante da derivação liquórica ventrículo-subcutânea (DVSC) (SANTOS et al, 2016 (BONDURANT et al, 1995;LAM et al, 2014). Williams et al (2007), definiram-na como um aumento do volume dos ventrículos cerebrais secundário à alteração da secreção, circulação ou reabsorção liquórica, resultando no aumento da pressão intracraniana (PIC) e surgimento de sintomas / sinais clínicos.…”
Section: Lista De Figurasunclassified
“…Surpreendentemente, considerando o número crescente de estudos relacionados à hidrocefalia experimental nos últimos anos, há poucas descrições publicadas de derivações experimentais (MILLER et al, 2007;ESKANDARI et al, 2012;CASTRO et al, 2012;CATALÃO et al, 2014). A técnica utilizada neste trabalho envolveu uma derivação entre os ventrículos laterais do animal e o espaço subcutâneo criado próximo a sua cauda, que se mostrou simples e confiável (SANTOS et al, 2016).…”
Section: Biomarcadores Na Hidrocefaliaunclassified
“…Após revisamos a técnica cirúrgica e o procedimento era realizado o fechamento da pele em plano único com prolene 5.0 (Figura 3). A técnica foi desenvolvida no laboratório de pesquisa, com o detalhamento dos procedimentos publicados recentemente(SANTOS et al, 2016). A avaliação pós-cirúrgica pode ser observada na figura 4.…”
unclassified